2022
DOI: 10.29408/veles.v6i1.5220
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Online Learning on Academic Writing Course During Covid-19 Pandemic

Abstract: Since the outbreak of Covid 19 in Indonesia, all universities, including Universitas Muhammadiyah Makassar, had made a decision for lecturers and students to learn from home (LFH) since March 16, 2020. This decision certainly has an impact on the change of the learning process which is used to face-to-face in the classroom then drastically changed and become online learning. This study aims at investigating the effectiveness of online learning on the Academic Writing course in the English Education Study Prog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 20 publications
1
5
0
Order By: Relevance
“…As indicated by the good outcome, the students' excitement for fiction stories motivated them to write a short story as part of their creative writing and fiction writing tasks. This finding is in line with Dewi et al (2022) who revealed that most of the students were interested in and preferred fiction story.…”
supporting
confidence: 89%
See 1 more Smart Citation
“…As indicated by the good outcome, the students' excitement for fiction stories motivated them to write a short story as part of their creative writing and fiction writing tasks. This finding is in line with Dewi et al (2022) who revealed that most of the students were interested in and preferred fiction story.…”
supporting
confidence: 89%
“…Moreover, writing helps in deepening knowledge, as pointed out by Graham & Perrin (2007). Nappu et al (2022) noted that students are familiar with different writing techniques and can produce clear and relevant paragraphs.…”
mentioning
confidence: 99%
“…E-learning is divided into synchronous and asynchronous (Amiti, 2020;Ogbonna et al, 2019). Synchronous occur at the same time that learning occurs at the same time that teachers and students are online, thus enabling direct interaction (Nappu et al, 2022). Meanwhile, asynchronous occurs at different times.…”
Section: Finding and Discussionmentioning
confidence: 99%
“…Hence, it will tangentially make it simpler for teachers to instruct students in the classroom and to meet their demands. The study by Nappu et al (2022), which discovered that employing technology in learning English had an impact on students' skills, particularly in writing descriptive paragraphs, serves as evidence for this claim. To effectively support teaching and learning, it is crucial to discover a way to incorporate technologies into a curriculum.…”
Section: Introductionmentioning
confidence: 96%